METHODS OF IMPROVING THE PROCESS OF TRAINING HIGHLY QUALIFIED PERSONNEL IN THE CONTEXT OF DIGITAL INNOVATION (Universal International Scientific Journal, 2026)
This article analyzes the theoretical and practical aspects of improving the process of training highly qualified personnel in digital innovation conditions. It is substantiated that modern digitalization processes are introducing new requirements and approaches to the education system. The study highlights the possibilities of using digital technologies, innovative pedagogical methods and software and platform tools in the effective organization of the personnel training process in higher educational institutions.Also, the mechanisms for forming professional competencies, developing independent learning and improving the quality of education in the conditions of digital transformation of the educational process are analyzed on a scientific and theoretical basis. The article reveals the criteria for selecting digital tools, their functional capabilities and practical effectiveness based on examples. The author substantiates the role and importance of digital educational technologies in training competitive, creative and highly qualified specialists in an innovative environment.
Keywords: Modern digitization, digital technology, specialist, innovative methods, highly qualified personnel, personnel training process, higher education system, improving the quality of education, innovative pedagogy.